KAJIAN KESELAMATAN KERJA NELAYAN PURSE SEINE DI PELABUHAN PERIKANAN SAMUDRA (PPS) KUTARAJA, BANDA ACEH - Riki Rinaldi; Chaliluddin Chaliluddin; Rian Juanda (Universitas Syiah Kuala, 2018)
ABSTRACTIn an effort to protect and guarantee the safety, security and comfort of fishing boat crew work, the operational safety factors of fishing vessels in the sea are very important to prioritize, especially the availability of ship safety equipment and conditions are good, so that if a ship accident occurs the safety equipment is ready to used. This study aims to determine the application of regulations related to work safety equipment and their availability on purse seine vessels in Kutaraja Fishing Port of Banda Aceh, and to know fishermen's perceptions of the importance of work safety equipment. This study uses direct survey methods and interviews with reference to existing national regulations, then the data are analyzed descriptively and linear regression analysis through the SPSS program. The results showed that from all samples of 11 GT- 61 GT (n = 21) vessels, the presence or application of safety equipment on purse seine vessels was 63%, in ships 11 GT-20 GT was 45% (n = 3) , for the 21 GT - 30 GT vessels the use of safety equipment is 60% (n = 6), the 30 GT - 50 GT vessels using safety equipment are 65% (n = 7), on ships 51 GT - 60 GT the use of safety equipment is 57% (n = 3) and on ships greater than 61 GT uses of safety equipment is 86% (n = 2), meaning that the average application is 62.6%. Fishermen already understand the importance of work safety equipment, but the availability and number of work safety equipment on board is inadequate. Work safety (independent) tools have an influence on the perception of fishermen (dependent) only by 1.83%, the rest 98.17% is influenced by other factors outside the availability of work safety equipment. The existence of available safety equipment in the purse seine ship consists of GPS devices, SSB radios, compasses, life jackets, life bouy, glasses, gloves, work shoes, winches, capstan, tools, first aid kits and light fire extinguishers (APAR).Keywords: Work safety, fishermen, Kutaraja fishing port, purse seine, perception, regulation ABSTRAKDalam upaya melindungi dan menjamin keselamatan, keamanan dan kenyamanan kerja awak kapal perikanan, maka faktor keselamatan operasional kapal perikanan di laut sangatlah penting untuk diprioritaskan, terutama ketersediaan alat keselamatan kapal harus tersedia dan kondisinya baik, sehingga bila terjadi kecelakaan kapal alat keselamatan kerja di kapal siap digunakan. Penelitian ini bertujuan untuk mengetahui penerapan regulasi terkait alat keselamatan kerja dan ketersediannya pada kapal purse seine di Pelabuhan Perikanan Samudera (PPS) Kutaraja, Banda Aceh serta mengetahui persepsi nelayan terhadap arti penting alat keselamatan kerja. Penelitian ini menggunakan metode survey langsung dan wawancara dengan mengacu pada regulasi-regulasi nasional yang ada, selanjutnya data dianalisis secara deskriptif dan analisis regresi linear melalui program SPSS. Hasil penelitian menunjukkan bahwa dari seluruh sampel kapal 11 GT- 61 GT (n = 21) keberadaan atau penerapan alat-alat keselamatan pada kapal purse seine adalah sebesar 63%, pada kapal 11 GT – 20 GT adalah sebesar 45% (n = 3), pada kapal 21 GT – 30 GT penggunaan alat keselamatan adalah sebesar 60% (n= 6), kapal 30 GT – 50 GT pengunaan alat keselamatan adalah sebesar 65% (n = 7), pada kapal 51 GT – 60 GT penggunaan alat keselamatan adalah 57% (n = 3) dan pada kapal ukuran lebih besar dari 61 GT penggunaan alat keselamatan adalah 86% (n = 2), artinya rata-rata penerapannya adalah 62.6%. Nelayan sudah memahami arti penting peralatan keselamatan kerja hanya saja ketersediaan dan jumlah alat keselamatan kerja di atas kapal yang belum memadai. Alat keselamatan (independen) kerja mempunyai pengaruh terhadap persepsi nelayan (dependen) hanya sebesar 1,83%, selebihnya sebesar 98,17% dipengaruhi oleh faktor lain di luar kesediaan alat keselamatan kerja. KeberadaanAlat-alat keselamatan yang tersedia dikapal purse seine terdiri dari alat GPS, radio SSB, kompas, life jacket, life bouy,kacamata, sarung tangan, sepatu kerja, derek, capstan, perkakas, P3K dan alat Pemadam api ringan (APAR). Kata Kunci: Keselamatan kerja, nelayan, PPS Kutaraja, purse seine, persepsi, regulasi.